2019
DOI: 10.5539/jas.v11n18p30
|View full text |Cite
|
Sign up to set email alerts
|

Azolla Fern in Mwea Irrigation Scheme and Its Potential Nitrogen Contribution in Paddy Rice Production

Abstract: Azolla fern is invasive in Mwea Irrigation Scheme in Kenya and its management in paddy rice fields is a challenge to farmers. A survey was undertaken to establish farmers’ knowledge and potential nitrogen contribution by Azolla in the paddies. The Scheme was stratified into seven sections and a questionnaire administered to 250 farmers. Data were collected on awareness levels, source, trend of infestation, abundance, fertilizer regimes and management practices. Five farms from each of the sections we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The Mwea region is located 100 km north of Nairobi and is a flat area extending to the south of Mount Kenya, the nation's highest mountain (5199 m). With an altitude of around 1159 m, the average annual temperature in the Mwea region is ~22 • C, and the average annual rainfall is ~930 mm [23]. The local climate is tropical with two rainy seasons: a long rainy season from March to May and a short one from October to November [24].…”
Section: Study Areamentioning
confidence: 99%
“…The Mwea region is located 100 km north of Nairobi and is a flat area extending to the south of Mount Kenya, the nation's highest mountain (5199 m). With an altitude of around 1159 m, the average annual temperature in the Mwea region is ~22 • C, and the average annual rainfall is ~930 mm [23]. The local climate is tropical with two rainy seasons: a long rainy season from March to May and a short one from October to November [24].…”
Section: Study Areamentioning
confidence: 99%
“…Ito and Watanabe (1985) showed that early incorporation of Azolla in the soil increases nitrogen availability. Farmers in Mwea incorporate Azolla in the soil during weeding as a management strategy (Oyange et al, 2019). Considering the abundance of Azolla in Mwea paddies, its integration with inorganic fertilizers and timely incorporation in the soil can help reduce the cost of inorganic fertilizers and consequently the cost of paddy rice production.…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic fertilizers that farmers mainly use in the MIS release mineral nitrogen in the form of NH 4 + , which is stable in ooded anaerobic environments. The nitrogen is usually applied in three splits whereby about 30% of the total nitrogen is applied as basal with the remaining amount applied in two equal splits at the active tillering and panicle initiation stage (Oyange et al 2019). Soil aeration due to draining of water cause changes in nitrogen from NH 4 + to NO 3 -; the latter nitrogen form is unstable under ooded anaerobic conditions and can quickly be lost through denitri cation (Ishii et al 2011).…”
Section: B Macro-nutrientsmentioning
confidence: 99%